Descending Aorta Calcinosis and Hypertension in Patients with Radiographic Axial Spondyloarthritis - Olena G. Aksonova; Gennadii D. Kirzhner; Yaroslav I. Smarovoz (Ukrainian Journal of Cardiovascular Surgery, 2024)
This article is the result of our own clinical observations and a literature search on the development of aortic calcification and hypertension syndrome in patients with axial spondyloarthritis, as well as the clinical significance of the combination of these pathologies and management thereof.The aim. To increase the awareness of practicing doctors regarding the possible association of aortic calcification and hypertension in patients with axial spondyloarthritis, their diagnosis and possible development mechanisms.Materials and methods. For this article we described two patients with axial spondyloarthritis, calcinosis of descending aorta and high blood pressure and conducted a case-based review of related literature.Results. The article presents the results of studies, where authors tried to explain possible mechanisms of development of aortic calcification and hypertension in patients with axial spondyloarthritis. Despite the fact that the data of these studies are scattered and researchers have not yet reached a certain consensus, the available results allow us to believe that patients with axial spondyloarthritis are at increased risk for the development of aortic calcification and hypertension syndrome. Given the possible consequences of these lesions, this cohort of patients requires increased attention from clinicians of various profiles.Conclusions. Aortic calcinosis can develop in patients with axial spondyloarthritis at its various stages, and also be one of the reasons for the development of high hypertension in such patients. We consider it expedient to conduct a routine examination of the aorta in patients with radiographic axial spondyloarthritis in case of detection of hypertension in them, because this group of patients has a pathophysiological basis for the calcification of vessels of the elastic type, which is given above. This will make it possible to correctly assess the patient’s cardiovascular risks, to draw up more correct plan for their long-term management by a cardiologist in cooperation with a rheumatologist and a cardiac surgeon, as well as to choose more effective therapy for blood pressure correction.